2015
DOI: 10.1371/journal.pone.0137820
|View full text |Cite|
|
Sign up to set email alerts
|

Fission Yeast CSL Transcription Factors: Mapping Their Target Genes and Biological Roles

Abstract: BackgroundCbf11 and Cbf12, the fission yeast CSL transcription factors, have been implicated in the regulation of cell-cycle progression, but no specific roles have been described and their target genes have been only partially mapped.Methodology/Principal FindingsUsing a combination of transcriptome profiling under various conditions and genome-wide analysis of CSL-DNA interactions, we identify genes regulated directly and indirectly by CSL proteins in fission yeast. We show that the expression of stress-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(78 citation statements)
references
References 65 publications
4
74
0
Order By: Relevance
“…Interestingly, a recent report suggested that the CSL transcription factor Cbf11 binds to the promoters of seven Mga2 target genes in S. pombe (56). Although cbf11 is not itself an Mga2 target gene (supplemental Table S4), deletion of cbf11 results in a low oxygen growth defect in our screen (supplemental Tables S1 and S2), and Cbf11 was found to bind Mga2 in an affinity capture screen for the fission yeast protein interactome network (57).…”
Section: Strainmentioning
confidence: 65%
“…Interestingly, a recent report suggested that the CSL transcription factor Cbf11 binds to the promoters of seven Mga2 target genes in S. pombe (56). Although cbf11 is not itself an Mga2 target gene (supplemental Table S4), deletion of cbf11 results in a low oxygen growth defect in our screen (supplemental Tables S1 and S2), and Cbf11 was found to bind Mga2 in an affinity capture screen for the fission yeast protein interactome network (57).…”
Section: Strainmentioning
confidence: 65%
“…An intriguing and still poorly understood aspect of the cut phenotype in S. pombe lipid metabolism mutants is the dependence of mitotic defects on the growth medium used. Whereas in the complex yeast extract with supplements (YES) medium the incidence of cut mitoses is high in cut6–621 and cbf11∆ mutants, the mitotic defects are largely suppressed when mutant cells are grown in the Edinburgh minimal medium (EMM) defined medium, or upon genetic disruption of nutrient‐sensitive signaling pathways of protein kinase A (Pka1) and stress‐activated protein kinase (Sty1/Spc1; Převorovský et al, ; Převorovský et al, ). We have recently shown that the crucial suppressive component of EMM is ammonium chloride, a good nitrogen source, suggesting that nitrogen source availability and/or nitrogen‐dependent signaling play an important role in the successful progression through mitosis in S. pombe (Zach et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Mga2 transcription factor is important for lipid homeostasis and shares a number of target genes with Cbf11. Also, the degrees of activatory contribution of Mga2 and Cbf11 seem to be similar for many of their shared target genes (Burr et al, ; Převorovský et al, ). Strikingly, no cut phenotype has been reported for the mga2∆ mutant.…”
Section: Cut Mutants Linked To Fatty Acid (Fa) Anabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was observed that the cut6 mutant phenotype, together with the “cut” phenotype caused by the deletion of the transcription factor cbf11 , can be suppressed by supplementation of the growth medium with ammonium chloride (Zach et al, ). Cbf11 is a transcription factor which regulates the expression of several genes involved in lipid metabolism, including cut6 (Prevorovsky et al, ; Prevorovsky et al, ). It is reasonable to assume that addition of ammonium chloride to the growth medium somehow helps to increase lipid metabolism of the cut6 mutants, thus supporting timely nuclear envelope expansion and faithful mitotic progression.…”
Section: Phospholipid Precursorsmentioning
confidence: 99%